„Wyznania antysemioty” — z semiotyki średniowiecznej kultury Europy Zachodniej - Jakóbczyk, Stanisław (Studia Europaea Gnesnensia, 2011)
The purpose of this paper is to discuss extreme views on the sign (interpretable, hermeneutic) character of “humanist objects”, the so called artefacts, and the abuse of methodological choices which produce them. Apart from several introductory sen-tences, I shall remain, however, concerned with these objects, the thing in itself, rather than pseudo-philosophical meanderings “beyond the thing”. Simply, I would like to provide several examples, arguments against the criticised views.inning of the 1930s. Some of the travellers visited the state seeking to be reassured in their negative opinion. Others, in contrast, went there convinced that they travelled to a country of universal social justice. However, they did not realise to what an extent the programme of their visit depended on the Soviet propaganda machine. The combined reading of texts by Antoni Słonimski, Andre Gide, Melchior Wańkowicz and Bernard Shaw shows the USSR as a country whose directions of development are difficult to foresee.